Is It the Twilight of BACE1 Inhibitors? - Hrabinova, Martina; Pejchal, Jaroslav; Kucera, Tomas; Jun, Daniel; Schmidt, Monika; Soukup, Ondrej (Current neuropharmacology, 2021)
β-secretase (BACE1) has been regarded as a prime target for the development of amyloid beta (Aβ) lowering drugs in the therapy of Alzheimer´s disease (AD). Although the enzyme was discovered in 1991 and helped to formulate the Aβ hypothesis as one of the very important features of AD etiopathogenesis, progress in AD treatment utilizing BACE1 inhibitors has remained limited. Moreover, in the last years, major pharmaceutical companies have discontinued clinical trials of five BACE1 inhibitors that had been strongly perceived as prospective. In our review, the Aβ hypothesis, the enzyme, its functions, and selected substrates are described. BACE1 inhibitors are classified into four generations. Those that underwent clinical trials displayed adverse effects, including weight loss, skin rashes, worsening of neuropsychiatric symptoms, etc. Some inhibitors could not establish a statistically significant risk-benefit ratio, or even scored worse than placebo. We still believe that drugs targeting BACE1 may still hide some potential, but a different approach to BACE1 inhibition or a shift of focus to modulation of its trafficking and/or post-translational modification should now be followed.
Keywords: Aspartic Acid Endopeptidases; Alzheimer’s disease; Alzheimerova nemoc; Alzheimer Disease; β-secretase; Prospective Studies; lidé; amyloidní beta-protein; amyloid beta; clinical trials; Amyloid beta-Peptides; sekretasy; inhibitors; aspartátové endopeptidasy; Humans; substrates; Amyloid Precursor Protein Secretases; prospektivní studie